2004
DOI: 10.1097/00002030-200406180-00013
|View full text |Cite
|
Sign up to set email alerts
|

Decreased apoptosis of bone marrow progenitor cells in HIV-1-infected patients during highly active antiretroviral therapy

Abstract: Impaired haematopoiesis during HIV-1 infection may be caused by the overproduction of inflammatory cytokines by immune cells at the bone marrow level inducing Fas-mediated apoptosis of stem progenitors. In this study, we evaluated the effects of highly active antiretroviral therapy on apoptosis of CD34+ stem cells derived from the bone marrow of HIV-1-infected patients, and observed decreased Fas expression on progenitor cells, in parallel with the diminution of TNF-alpha levels and the amelioration of clonoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 8 publications
1
14
0
Order By: Relevance
“…20,21 One possible mechanism for this effect is an increase in Fas-mediated apoptosis of CD34 ϩ progenitor cells in the bone marrow due to HIV-1 infection resulting in loss of progenitor cells, which can be remedied with HAART. 20 Similar results have been seen in HIV-infected chimpanzees. 21 Research in the United States using HIV-1-infected and -uninfected human bone marrow found an association with CD34/CD4 ϩ % in the bone marrow and circulating CD4 counts.…”
Section: Figsupporting
confidence: 71%
“…20,21 One possible mechanism for this effect is an increase in Fas-mediated apoptosis of CD34 ϩ progenitor cells in the bone marrow due to HIV-1 infection resulting in loss of progenitor cells, which can be remedied with HAART. 20 Similar results have been seen in HIV-infected chimpanzees. 21 Research in the United States using HIV-1-infected and -uninfected human bone marrow found an association with CD34/CD4 ϩ % in the bone marrow and circulating CD4 counts.…”
Section: Figsupporting
confidence: 71%
“…25,29,30 Work by multiple groups has shown that hematopoietic function can be at least partially restored with the use of highly active antiretroviral therapy (HAART). [31][32][33][34][35][36][37] The findings described here indicate that HIV-1C can infect HPC-CFUs and CD34 ϩ HPCs in vitro and in vivo, and that this infection is associated with higher anemia rates in infected patients. Taken with our previous results, this indicates that the effect of Data are numbers of infected colonies over numbers of single colonies tested.…”
Section: Discussionmentioning
confidence: 97%
“…10 The introduction of highly active antiretroviral therapy (HAART) regimens in the mid-1990s dramatically changed many aspects of living with HIV infection, including drastic improvements in hematopoiesis. 11 Although HAART clearly ameliorates HIVassociated hematosuppression, blood cell development is not completely restored. 12 Moreover, long-term toxicity concerns are spurring the idea of moving treatment away from drug therapy.…”
Section: Introductionmentioning
confidence: 99%